POSTER KIMIA UNSUR UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA SMA NEGERI 1 PEKANBARU - Agustina Agustina; Uji Niantari; Roza Linda (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Riau (UNRI), 2017)
This study aims to determine the implementation of process and activity learning used chemical poster elements to improve students learning activities in senior high school 1 in Pekanbaru in chemical elements subject. The method used an action research that consists of four stages: planning, implementation, observation and reflection. Responden were students of class XII MIA 7 Senior high school 1 in Pekanbaru. The indicators research was the implementation of chemical elements according to the poster as syntax, student activities during the learning process was able to achieve both categories. The research instrument used question for post test and student activity observation sheet. The results showed that the learning activities using chemical poster elements are at a good stage with achievement, in the first cycle was 60.67% and the second cycle was 68.08%.